Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/jcm11051446
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Occurrence of Healthcare-Associated Infections in Patients with and without COVID-19 Hospitalized during the Pandemic: A 16-Month Retrospective Cohort Study in a Hospital Intensive Care Unit

Abstract: The COVID-19 pandemic has increased the healthcare-associated infection (HAI) risk in intensive care unit (ICU) patients. However, a comparison between patients with and without COVID-19 in terms of HAI incidence has been rarely explored. In this study, we characterized the occurrence of HAI among patients with and without COVID-19 admitted to the ICU of the Umberto I hospital of Rome during the first 16 months of the pandemic and also identified risk factors for HAI acquisition. Patients were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Slovakia was hard hit by the COVID-19 epidemic mainly at the end of 2020 and in early 2021, when the number of new cases rapidly increased, and patients at risk of dying began to exceed the capacities of hospitals [19]. Based on our findings, CLABSI rates were consistent with the worsening COVID-19 epidemiological situation, and the same results were presented in other studies [25,30].…”
Section: Discussionsupporting
confidence: 88%
“…Slovakia was hard hit by the COVID-19 epidemic mainly at the end of 2020 and in early 2021, when the number of new cases rapidly increased, and patients at risk of dying began to exceed the capacities of hospitals [19]. Based on our findings, CLABSI rates were consistent with the worsening COVID-19 epidemiological situation, and the same results were presented in other studies [25,30].…”
Section: Discussionsupporting
confidence: 88%
“…In general, previous studies have indicated that COVID-19 patients are at increased risk, relative to non-COVID-19 patients, for hospital-onset MDRO HAIs. [22][23][24][25][26][27][28] Superinfection with MDRO S. aureus has been described in previous reports describing HAI incidence in COVID-19 patients. 8,14 Superinfection with MDRO S. aureus have been directly attributed to the management of COVID-19 patients, which often included used of catheters, intubation, and corticosteroid use.…”
Section: Discussionmentioning
confidence: 99%
“…Among the indirect consequences of the COVID-19 pandemic, an increase in the incidence of HAIs has been frequently reported, especially in some wards, such as ICUs [ 11 , 22 ]. However, most studies have focused on adult ICUs, while data on the impact of the pandemic on HAIs in NICUs are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…While the impact of the pandemic on incidence rates of nosocomial infections in adult ICUs has been investigated [ 6 , 11 , 12 , 13 ], data from the NICU setting are scarce. A few indirect effects of the pandemic on NICUs have been described, such as psychological distress or obstacles in implementing family-centered care [ 14 ].…”
Section: Introductionmentioning
confidence: 99%